THE CONCEPT OF RELIGIOSITY OF MUSLIM MARRIED COUPLES IN MAINTAINING HOUSEHOLD HARMONY IN THE PERSPECTIVE OF THE QURAN: A THEMATIC INTERPRETATION STUDY - Winning Son Ashari; Sudirman; Miftahul Huda; Cindy Eka Ananda Pangestu (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2026)
Marriage in Islam is not merely a social institution but also a spiritual bond aimed at achieving sakinah, mawaddah, and raḥmah. Amid increasing household conflicts and shifting moral values in modern society, the role of religiosity becomes essential in maintaining family harmony. This study examines the concept of religiosity among Muslim married couples from the Qur’anic perspective using a thematic interpretation approach. Employing qualitative library research, the study analyses relevant Qur’anic verses alongside classical and contemporary tafsīr literature. The findings reveal that the Qur’an presents marital religiosity as a multidimensional concept grounded in Islām, Īmān, and Iḥsān, and strengthened by the awareness of divine supervision (murāqabah). A religious husband is characterised by devotion to Allah, responsible leadership, patient religious guidance, kind treatment based on Sharīʿah and sound social custom (ʿurf), and financial responsibility according to his ability. Meanwhile, a religious wife is characterised by obedience to Allah and to her husband within the limits of Sharīʿah, as well as by safeguarding her husband’s rights and honour. The study concludes that such religiosity leads to household harmony through divine guidance, righteous family life, moral improvement, and ease in facing life’s difficulties. This research offers a holistic Qur’anic framework for building harmonious Muslim families.